Integrating architectural design to the clinical areas of a hospital - Mohd Nawawi, Norwina (2009)
The presentation provide an overview of hospital planning and design to with emphasis on the need to integrate design aesthetics to clinical settings. Case studies of hospitals in the country and abroad are potrayed in the lecture.